Analysing social presence in Whatsapp application using LIWC analysis - Siti Norzaimalina, Abd Majid; Abdul Rahim, Salam (Universiti Teknologi Malaysia, 2023)
Instant messaging platforms such as WhatsApp has become a popular mode of communication adopted in online learning. A high level of social presence is essential for online learning to be effective. While many studies have explored social presence in various online contexts, there is a gap in understanding the linguistic elements that indicate social presence using computerised text analysis programs like Linguistic Inquiry and Word Count (LIWC). Therefore, this study aims to analyze social presence, specifically in WhatsApp, using the LIWC program. Seven linguistic categories from LIWC, namely clout, authentic, tone, negative emotions, positive emotions, social processes, and first pronoun (I, We), were chosen as social presence indicators. WhatsApp conversations from four groups of postgraduate students were selected in this study. Generally, the average word count for a 17-week conversation was 3861 words per group. The groups showed a high confidence level and expertise (clout) in WhatsApp conversations. However, they used a distanced form of discourse in their messages (authentic). The conversational tone was upbeat style and positive (tone). The first pronoun ‘we’ was used more than “I”. About 7% of overall messages were positive, and only 1% of negative emotions. Meanwhile, social processes portrayed were about 13% in general. This study highlights that linguistic elements can be used to imply the existence of social presence in WhatsApp, leading to more data-driven insights. Furthermore, educators and instructional designers can enhance the online learning experience by incorporating strategies that foster positive linguistic elements associated with social presence. This could involve engaging in collaborative discussions and creating an environment that encourages positive emotions and open communication. Further research could explore the relationship between linguistic elements and other types of presence, such as cognitive and teaching presence, in different communication contexts.